Multidisciplinary Management of Disorders of Sex Development in Indonesia, A Prototype in Developing Country - Nurin Aisyiyah Listyasari; Ardy Santosa; Achmad Zulfa Juniarto; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2017)
Background : Disorder of sex development (DSD) patients require comprehensive management to improve quality of life. A standardized management protocol for patients in Indonesia is not yet available resulting in patients infrequently received a proper diagnosis. This study reported a multidisciplinary management DSD in Indonesia based on minimal diagnostic facilities and expertise in developing country.Objectives : The purpose of the study is to review the management of DSD patients in Indonesia relates to providing appropriate gender assignment and to improving patients quality of life.Methodology : We analyzed the records of DSD patient admitted to the division of Human Genetics Center for Biomedical Research (CEBIOR) Faculty of Medicine Diponegoro University, Semarang, Indonesia from May 2004 - December 2015. Data were collected and analyzed for physical examination, family pedigree karyotyping, hormonal assays and psychosocial. Other examination such as ultrasonography, Xray and Cytoscopy were also recorded for selected cases. Bimonthly, Sexual Adjustment Team (SAT) meeting was recorded.Results : From the total 617 DSD cases we found 426 cases (69,04 %) with 46, XY DSD, 117 cases (18,96%) with 46,XX DSD and 74 cases (12%) with sex chromosome DSD. Most of the patients in the group of 46, XY DSD are Unknown Male Undervirilization (UMU) with 256 cases (60.09%). As the majority cases of 46, XX DSD was Congenital Adrenal Hyperplasia with 81 cases (69.23%). The remaining cases were Androgen Action Disorder (AAD) with 140 cases (32.86%), 46, XY DSD Gonadal Dysgenesis with 30 cases (7.04%), Androgen Excess Disorders with 3 cases (2.56%), Defect of Mullerian Development with 19 cases (16,24%), 3 cases (2.56%) of Androgen Excess and 3 cases (2.56%) of 46, XX Gonadal Dysgenesis.Conclusion : Comprehensive management for DSD Patients help patient in diagnosis, gender assignment and support patient to improve quality of life. This multidisciplinary of DSD team is the only team in Indonesia that can be used as a model for other center in Indonesia as well as other developing countries with minimal diagnostic facilities.